ER-tethered RNA-binding protein controls NADPH oxidase translation for hydrogen peroxide homeostasis - Xintong Pei; Zhe Wang; Wenting He; Shunqin Li; Xiaowei Chen; Zhen Fan; Yongguang Lan; Lin Yuan; Pingyong Xu (Redox Biology, 2024)
Hydrogen peroxide (H2O2) functions as a signaling molecule in diverse cellular processes. While cells have evolved the capability to detect and manage changes in H2O2 levels, the mechanisms regulating key H2O2-producing enzymes to maintain optimal levels, especially in pancreatic beta cells with notably weak antioxidative defense, remain unclear. We found that the protein EI24 responds to changes in H2O2 concentration and regulates the production of H2O2 by controlling the translation of NOX4, an enzyme that is constitutively active, achieved by recruiting an RNA-binding protein, RTRAF, to the 3′-UTR of Nox4. Depleting EI24 results in RTRAF relocating into the nucleus, releasing the brake on NOX4 translation. The excessive production of H2O2 by liberated NOX4 further suppresses the translation of the key transcription factor MafA, ultimately preventing its binding to the Ins2 gene promoter and subsequent transcription of insulin. Treatment with a specific NOX4 inhibitor or the antioxidant NAC reversed these effects and alleviated the diabetic symptoms in beta-cell specific Ei24-KO mice. This study revealed a new mechanism through which cells regulate oxidative stress at the translational level, involving an ER-tethered RNA-binding protein that controls the expression of the key H2O2-producing enzyme NOX4.